2022
DOI: 10.3390/diagnostics12051164
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantum Magnetic IL-6 Point-of-Care Assay in Patients Hospitalized with COVID-19

Abstract: Interleukin-6 (IL-6) has been linked to several life-threatening disease processes. Developing a point-of-care testing platform for the immediate and accurate detection of IL-6 concentrations could present a valuable tool for improving clinical management in patients with IL-6-mediated diseases. Drawing on an available biobank of samples from 35 patients hospitalized with COVID-19, a novel quantum-magnetic sensing platform is used to determine plasma IL-6 concentrations. A strong correlation was observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In another demonstration, NV-based magnetic microscopy was applied to detect concentrations of magnetically labelled protein, interleukin-6 65 , from patients hospitalized with COVID-19. Interleukin-6 is an endogenous cytokine associated with various diseases, such as severe COVID-19.…”
Section: Nv-based Magnetic Sensing and Imaging Of Cells And Tissuesmentioning
confidence: 99%
“…In another demonstration, NV-based magnetic microscopy was applied to detect concentrations of magnetically labelled protein, interleukin-6 65 , from patients hospitalized with COVID-19. Interleukin-6 is an endogenous cytokine associated with various diseases, such as severe COVID-19.…”
Section: Nv-based Magnetic Sensing and Imaging Of Cells And Tissuesmentioning
confidence: 99%
“…Spatial isolation of labels Detection of many single labels Enzymes confined in wells 8 or droplets 76 Microwell arrays 55,140 Wide FOV, high resolution multi-wavelength imaging 69 Amplification of nucleic acid labels in droplets 64 Arrays of droplets 77 Flow combined with laser-induced fluorescence 43 Labels directly associated with beads 60,63 Flow of droplets 59 Electrical 126 Nanoparticles 33, 103 Random dispersed arrays 62 Wide FOV plasmonic imaging 104 DNA nanostructures 127 Nanopore arrays 126 Scatter imaging 119 Laser induced fluorescence of bound labels 39 Flow cytometry 60 Coincidence detection 113 Laser induced fluorescence of released labels 42 Nanostructured surfaces 135 Time-resolved fluorescence (TIRF) microscopy 37 Particle motion 119,120 Mass spectrometry 142 Differential kinetics of specifically bound labels 123 Transmission electron microscopy 113 Nanopore blockade 125 Surface plasmon imaging 123 Nanopore translocation 127 Microbubbles 137 Diamond nitrogen vacancy centers 141 digital droplet immuno-PCR (ddIPCR). They formed oligonucleotide-labeled immunocomplexes at the surface of an ELISA plate, chemically released the label from the surface, partitioned the labels into droplets using a commercial droplet generator, performed PCR on the droplets, and then analyzed the on/off status of the droplets using a commercial droplet reader.…”
Section: Discrimination Of Single Labelsmentioning
confidence: 99%
“…For example, Wang et al 139 and Piraino et al 140 have used pneumatic sealing of PDMS microwell arrays against glass surfaces in integrated microfluidic devices to digitize immunocomplexes formed on planar surfaces. Atallah et al 141 reported the detection of single immunocomplexes using diamond nitrogen vacancy centers, where two different magnetic bead labels on the antibodies that respond differently to the magnetic field can, therefore, make use of coincidence optical detection. They used this approach to develop an assay for IL-6 with an LOD of 2 fM to measure the protein in the serum of COVID-19 patients.…”
Section: Emerging Approaches To Digital Protein Detectionmentioning
confidence: 99%
“…As an endogenous cytokine, interleukin-6 (IL-6) has been linked to many inammatory diseases, such as chronic obstructive pulmonary disease. 1,2 The detection of IL-6 in serum plays a signicant role in disease diagnosis and prognosis. [3][4][5] Therefore, the development of sensors for the rapid and accurate detection of IL-6 has great signicance.…”
mentioning
confidence: 99%